Methane hydrate regasification to intensify the combustion of low-rank coal fuels - Vinogrodskiy K. Kirill; Nagibin P. S. Pavel Sergeevich; Misyura S. Ya. Sergey Yakovlevich; Morozov V. S. Vladimir Sergeevich; Shlegel N. E. Nikita Evgenjevich; Strizhak P. A. Pavel Alexandrovich (2025, 2025)
Title screen.